rationalize
![( \sqrt{2} + \sqrt{3} ) \div (3 \sqrt{2} - 2 \sqrt{3} ) ( \sqrt{2} + \sqrt{3} ) \div (3 \sqrt{2} - 2 \sqrt{3} )](https://tex.z-dn.net/?f=%28+%5Csqrt%7B2%7D++%2B++%5Csqrt%7B3%7D+%29+%5Cdiv+%283+%5Csqrt%7B2%7D++-+2+%5Csqrt%7B3%7D+%29)
Answers
Answered by
0
Multiply by 3√2+2√3
*The denominator then rationalizes*
→(3√2-2√3)×(3√2+2√3)
→(3√2)²-(2√3)²
→18-12
→6
→Denominator becomes 6
*As we multiplied 3√2+2√3 in denominator,we have to multiply it in numerator too*
→(2√3)×(3√2+2√3)
*this can be left here as we have to Rationalize the Denominator*
→![\frac{2 \sqrt{3}×3 \sqrt{2}+2 \sqrt{3}}{6} \frac{2 \sqrt{3}×3 \sqrt{2}+2 \sqrt{3}}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B2+%5Csqrt%7B3%7D%C3%973+%5Csqrt%7B2%7D%2B2+%5Csqrt%7B3%7D%7D%7B6%7D+)
Similar questions
Computer Science,
6 months ago
Math,
6 months ago
Accountancy,
1 year ago
Computer Science,
1 year ago
English,
1 year ago